Acetylenic Replacement of Albicidin's Methacrylamide Residue Circumvents Detrimental E/Z Photoisomerization and Preserves Antibacterial Activity. Issue 35 (21st May 2021) - Behroz, Iraj; Kleebauer, Leonardo; Hommernick, Kay; Seidel, Maria; Grätz, Stefan; Mainz, Andi; Weston, John B.; Süssmuth, Roderich D.
Abstract: The natural product albicidin is a highly potent inhibitor of bacterial DNA gyrase. Its outstanding activity, particularly against Gram‐negative pathogens, qualifies it as a promising lead structure in the search for new antibacterial drugs. However, as we show here, the N‐terminal cinnamoyl moiety of albicidin is susceptible to photochemical E / Z isomerization. Moreover, the newly formed Z isomer exhibits significantly reduced antibacterial activity, which hampers the development and biological evaluation of albicidin and potent derivatives thereof. Hence, we synthesized 13 different variants of albicidin in which the vulnerable para ‐coumaric acid moiety was replaced; this yielded photostable analogues. Biological activity assays revealed that diaryl alkyne analogues exhibited virtually undiminished antibacterial efficacy. This promising scaffold will therefore serve as a blueprint for the design of a potent albicidin‐based drug. Abstract : Lead optimization : The cinnamoyl residue of the antibiotic albicidin is shown to readily undergo UV‐mediated E / Z isomerization, thereby converting from the highly bioactive E form found in the natural product to the significantly less bioactive Z form. Acetylenic replacement of the susceptible methylacrylamide moiety affords a set of photochemically stable albicidin derivatives with virtually undiminished antibacterial activity.